2015
DOI: 10.56431/p-e276tc
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Plant Density of Okra and Intercropping Effects on Yields of Egusi Melon-Okra Mixture, at Makurdi, Nigeria

Abstract: A field experiment was conducted from August to November, during the 2012 and 2013 cropping seasons at the Research Farm, University of Agriculture, Makurdi, Nigeria, to identify the optimum plant density of okra and intercropping effects on yields of egusi melon-okra mixture and to assess the yield advantages of the intercropping system. The experiment was a 3x3 split plot arrangement of treatments, fitted in a randomized complete block design (RCBD), replicated four times. The intercropping (sole egusi melon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Previous studies demonstrated that the values of CR for maize were always more competitive than other crops such as rajmash (Kour et al, 2016) and soybean (Wei et al, 2022). Also, Ijoyah et al (2012) found that intercropping maize at high plant density 50000 maize plants/ha with okra recorded the lowest competitive ratio (0.65) compared to the low and medium plant density (33000 and 40000 maize plants/ha).…”
Section: -3 Competitive Ratio (Cr)mentioning
confidence: 87%
See 1 more Smart Citation
“…Previous studies demonstrated that the values of CR for maize were always more competitive than other crops such as rajmash (Kour et al, 2016) and soybean (Wei et al, 2022). Also, Ijoyah et al (2012) found that intercropping maize at high plant density 50000 maize plants/ha with okra recorded the lowest competitive ratio (0.65) compared to the low and medium plant density (33000 and 40000 maize plants/ha).…”
Section: -3 Competitive Ratio (Cr)mentioning
confidence: 87%
“…Similar results were obtained by previous studies who found that the values of LER was increased more than one by intercropping maize + guar , maize + cowpea (Elsaid et al, 2019), maize + soybean (Abd Rabboh et al, 2020 andWei et al, 2022), teosinte + cowpea (Salem et al, 2019) and millet + cowpea (Mohamed et al, 2020) as compared to their sole croppings. Moreover, other investigators found that the values of LER were increased by increasing plant density of maize intercropped with soybean (Bechem et al, 2018) and with okra (Ijoyah et al, 2012).…”
Section: -4 Land Equivalent Ratio (Ler)mentioning
confidence: 90%
“…Most tropical intercropping systems have been found to contain maize as a common element (Ijoyah and Fanen, 2012). According to Adesoji et al, (2013), the nitrogen effects increase maize development by causing an increase in the cell division and expansion as well as an increase in the size of all of its morphological components.…”
Section: Effect Of Treatments On Maize Vegetative Parameters and Yieldmentioning
confidence: 99%
“…Maize and bean in Tanzania are produced in sole or mostly mixed between them or with other crops especially in smallholder farmers. Based on the marginal lands owned by most farmers in Tanzania, mixed cropping of two or more crops during the same growing season is because a common practices and this is driven by increases land productivity determined by land equivalent ratio [10], [20], [21]. Intercropping soybean and maize gave land equivalent ratio greater than one, indicating high productivity per unit area achieved by growing the two crops together [21].…”
Section: Introductionmentioning
confidence: 99%